Study of the equilibriums phases in the binary system for Sodium molybdate and lead molybdate (Na2MoO4– pbMoO4) (Latakia University Journal -Basic Sciences Series, 2018)
Lead and sodium molybdates form one of the most promising chemical compounds because of their various and important properties when used in many different technological applications such ceramic preparation, melting resistance materials and used in solar energy applications.This research aims to study the equilibriums phases in the binary system of sodium molybdate with lead molybdate. We used there for tow techniques :The technique of    X-ray diffraction, and technique of differential thermal analysis to study some physical properties.The result of this research was the obtaining of a solid solution based on a lead molybdates, where the sodium molybdate is dissolved in the lead molybdateup to        40 %  molar percentage.